Importance of Stock Market In India: A Review - Shubham Godbole (AG Volumes, 2021)
Volatility in the stock market refers to the fluctuation of stock prices over time. Mergers and acquisitions are often used by Indian firms to broaden their worldwide reach. Shareholders benefited from the growth of businesses by receiving excellent dividends and seeing their investment increase in value. As more initial public offerings (IPOs) enter the market, the number of businesses that are listed on the stock exchanges (BSE and NSE) grows. The Indian stock market is a diverse marketplace where investors may find many opportunities to make money. The focus of this article is on what makes the Indian stock market so significant. Many additional aspects are also included in this study.